Intrapulmonary Pharmacokinetics of S-013420, a Novel Bicyclolide Antibacterial, in Healthy Japanese Subjects - Furuie, Hidetoshi (American Society for Microbiology (ASM), 2010)
S-013420 (EDP-420) is a novel bicyclolide (bridged bicyclic macrolide) antibacterial currently under development for the treatment of respiratory tract infections. The objective of the present study was to determine the plasma and intrapulmonary pharmacokinetic parameters of orally administered S-013420 in healthy volunteers. Twenty-eight healthy Japanese male subjects who never smoked were randomly allocated to seven groups of four subjects each who underwent bronchoalveolar lavage (BAL) at different times after dosing (2, 4, 6, 8, 10, 12, or 24 h). Blood samples were also taken at 0, 0.5, 1, 2, 4, 6, 8, 10, 12, 24, 48, and 72 h after dosing. The S-013420 concentrations in plasma, epithelial lining fluid (ELF), and alveolar macrophages (AMs) were measured by using a combined high-performance liquid chromatography-mass spectrometric technique. A pharmacokinetic analysis of the plasma, ELF, and AM S-013420 concentration profiles was performed. S-013420 was rapidly absorbed in plasma, and the mean time to the maximum concentration in plasma was 2.27 h. S-013420 was rapidly distributed to the ELF and was slowly distributed to AMs. The areas under the concentration-time curves from time zero to 24 h (AUC(0-24)) for S-013420 were 20.3 times higher in ELF than in plasma and 244.6 times higher in AMs than in plasma. The mean maximum concentration in plasma was higher in ELF than in plasma and was much higher in AM than in plasma. Furthermore, pharmacodynamic calculations were done by using the AUC(0-24)/MIC(90) ratio for common pneumonia pathogens (Staphylococcus aureus, Streptococcus pneumoniae, Haemophilus influenzae, and Moraxella catarrhalis). The AUC(0-24) for plasma/MIC(90)s for these four organisms were 41.8, 83.6, 1.3, and 20.9, respectively. The AUC(0-24) for ELF/MIC(90)s were 849.6, 1,699.2, 26.6, and 424.8, respectively. Considering the good efficacy shown in a subsequent phase 2 study (S. Kohno, K. Yamaguchi, Y. Tanigawara, A. Watanabe, A. Aoki, Y. Niki, and J. Fujita, Abstr. 47th Intersci. Conf. Antimicrob. Agents Chemother., abstr. L-485), the good distribution of S-013420 in AMs and ELF observed in the present study is predictive of the good efficacy of S-013420 against respiratory pathogens.